APPLICATION OF DISTANCED EDUCATION TECHNOLOGIES - Калиниченко, О.В.; Назмутдинов, Р.А.; Ахметбекова, З.Д. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2024)
This article discusses the psychological and pedagogical features of distance educational technologies. The requirements that distance technologies impose on participants of the educational process are noted. It is noted that a high level of educational motivation can contribute to the development of abilities that are formed and manifested in educational activities.
Keywords: distance educational technologies; educational motivation; distance education